Temporal analysis of GLOFs in high-mountain regions of Asia and assessment of their causes - Kristýna Falátková (Acta Universitatis Carolinae Geographica, 2016)
Glacial lake outburst flood (or shortly GLOF) has become a well-known phenomenon, one of natural hazards occurring in glaciated high mountain areas of the world. The aim of this study was to investigate temporal distribution of these events in Asia and to assess causes of lake outbursts. Therefore, a search of scientific literature and reports was carried out resulting in 219 flood cases found. In order to detect possible differences in temporal distribution a group of ice-dammed lakes was detached and compared with the rest. Concerning spatial distribution of GLOFs, it is influenced by availability of scientific literature which is determined by research teams’ region interest. Temporal analysis revealed a certain pattern in ice-dammed lake outburst distribution and notable difference between the two lake groups in terms of outburst occurrence within a year. The moraine-dammed lake outbursts were recorded earlier in an ablation season (compared to ice-dammed lakes) which could be attributed to different mechanism of dam failure. Majority of lake outburst causes were included in the category of dynamic causes (e.g. ice avalanche), long-term causes (e.g. dead-ice melting) were less represented. Results of the study imply there can be notable variations of temporal distribution and causes of GLOFs among individual mountain regions even within one continent. Therefore, varying behavior of potentially dangerous lakes should be taken into consideration when, for instance, proposing mitigation measures.